Markers for Guillain‐Barré syndrome with poor prognosis: a multi‐center study. Issue 4 (11th September 2017) - Yamagishi, Yuko; Suzuki, Hidekazu; Sonoo, Masahiro; Kuwabara, Satoshi; Yokota, Takanori; Nomura, Kyoichi; Chiba, Atsuro; Kaji, Ryuji; Kanda, Takashi; Kaida, Kenichi; Ikeda, Shu‐ichi; Mutoh, Tatsuro; et al.
Abstract: Guillain‐Barré syndrome (GBS) is an acute monophasic neuropathy. Prognostic tools include the modified Erasmus GBS outcome score (mEGOS), Erasmus GBS respiratory insufficiency score (EGRIS), and the increase in serum IgG levels (ΔIgG) 2 weeks after intravenous immunoglobulin (IVIg) treatment. Given that proportions of GBS subtypes differ between Western countries and Japan, the usefulness of these tools in Japan or other countries remains unknown. We enrolled 177 Japanese patients with GBS from 15 university hospitals and retrospectively obtained mEGOS and EGRIS for all and ΔIgG status for 79 of them. High mEGOS scores on admission or on day 7 were significantly associated with poorer outcomes (unable to walk independently at 6 months). High EGRIS scores (≥5 points) were associated with an increased risk for mechanical ventilation. Patients with ΔIgG <1, 108 mg/dl had significantly poorer outcomes. We suggest that mEGOS, EGRIS, and ΔIgG in GBS are clinically relevant in Japan.